Structural Patterns and Narrative Presence: A Quantitative Study of Character Types and Story Arcs in Ama Ata Aidoo’s No Sweetness Here. - Kumar, Ajay; Chakrabarti, Dipa (Journal of Neonatal Surgery, 2025)
This article offers a quantitative structural analysis of Ama Ata Aidoo’s No Sweetness Here, a foundational collection of eleven stories depicting the social, emotional, and political realities of postcolonial Ghana. This study codes narrative variables of interest — the elements of narrative voice, dominant mode, protagonist gender, protagonist class, setting, time span, and ending types — in each of the stories, using Microsoft Excel as the primary analytical tool. The results also reveal that female characters are not only the most frequent — they’re also structurally central; they often function as emotional anchors in stories of loss, silence and resilience. Tragic, ambivalent endings are the most common, especially for stories about rural or working-class women, while redemptive endings are rare and hard-earned. The first-person narration, accompanied by dialogue-heavy passages of prose and compressed stretches of time and space, is an old trick of the trade for Aidoo, a vestige from the oral tradition of African storytelling, that allows for intimate access to her characters’ psychological and cultural conflicts. This study melds literary formalism and empirical content analysis to show that Aidoo’s storytelling choices are deliberate tools of gendered critique and socio-political commentary. This paper contributes to feminist narratology, African literary studies, and the emerging integration of quantitative methods into literary scholarship.